1997
DOI: 10.1159/000237550
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Production, Characterization and IgE Cross-Reactivity of Different Manganese Superoxide Dismutases in Individuals Sensitized to <i>Aspergillus fumigatus</i>

Abstract: Background: Manganese superoxide dismutase (MnSOD) from Aspergillus fumigatus has been demonstrated to be an allergen showing a high degree of homology with phylogenetically distant MnSODs. We describe cloning, production and characterization of MnSODs from different species. Methods: MnSODs were cloned by PCR, expressed as inclusion body protein in Escherichia coli, purified by Ni2+-chelate affinity chromatography and characterized. Results: The MnSODs from A. fumigatus, man, yeast, Drosophila mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 5 publications
2
46
0
Order By: Relevance
“…In the case of recombinant MnSOD, a native-like conformation could be confirmed by measurement of the enzymatic activity of the protein. Moreover, inhibition experiments using different MnSODs and serum of individuals sensitized to A. fumigatus MnSOD showed that the enzymes share common IgE-binding epitopes (14). Sequential site-directed mutagenesis of the conserved, surface-displayed amino acid residues described above will allow experimental determination of the contribution of each single residue to the clinically observed crossreactivity of A. fumigatus-allergic individuals toward MnSODs from different species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of recombinant MnSOD, a native-like conformation could be confirmed by measurement of the enzymatic activity of the protein. Moreover, inhibition experiments using different MnSODs and serum of individuals sensitized to A. fumigatus MnSOD showed that the enzymes share common IgE-binding epitopes (14). Sequential site-directed mutagenesis of the conserved, surface-displayed amino acid residues described above will allow experimental determination of the contribution of each single residue to the clinically observed crossreactivity of A. fumigatus-allergic individuals toward MnSODs from different species.…”
Section: Discussionmentioning
confidence: 99%
“…The protein was reconstituted by dialysis against water containing 0.1 mM MnCl 2 . Molecular size and purity were analyzed by denaturing, reducing SDS-PAGE and native-like folding was confirmed by determination of the enzymatic activity (14). For crystallization experiments the recombinant protein was concentrated to 15 mg/ml by ultrafiltration (Centrex UF-2; Schleicher & Schuell, Dassel, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…allergen.org). Most of the identified allergens elicit humoral immune responses [26][27][28][29], others are toxic to PBMC or are strongly homologous to human proteins, while some appear to prime primarily a Th2 T cell response [30][31][32][33]. Two allergens have been shown to stimulate both T and B cell responses from patients with ABPA, Asp f2 and Asp f16 [34,35].…”
Section: I I Introductionmentioning
confidence: 99%